ANALISIS PENGARUH KONDISI SOSIAL EKONOMI ORANG TUA TERHADAP PROSES DAN CAPAIAN PEMBELAJARAN SISWA DI SD - Alisah, Alisah; Zakiah, Linda; Prastiwi, Dinda Astria; Salim, Salsabila Nuramalia; Putri, Meisya Tania; Maulidya, Aisyah (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2025)
This study aims to analyze the influence of parents' socio-economic conditions on the learning process and academic achievement of elementary school students. This research is a descriptive qualitative study using a literature review method, in which the researcher collects and examines various relevant journal sources. The focus of this study is on the socio-economic background of parents, including education level, occupation, and income, in relation to student engagement during the learning process and the outcomes achieved. The results indicate that parents' socio-economic factors have a significant impact on students' learning motivation. Students from families with stable socio-economic conditions tend to have better access to education due to adequate supporting facilities and higher learning motivation. These findings highlight the importance of the family's role in shaping students’ learning enthusiasm in elementary school.